Radiosurgery treatment of brain metastasis: the relation of histology, brain location and symptoms - Gomes, Joana C. (2012)
Objective – To characterize clinically and statistically patients with brain metastases who underwent radiosurgery. Methodology – Retrospective analysis of patients with brain metastases that underwent linear accelerator-based radiosurgery in Hospital do Meixoeiro, and the information analyzed in SPSS version 18. Results – Were evaluated 116 patients with brain metastases. Primary tumors of the lung (54.30%) and breast (21.60%) were predominant. Symptoms that stood out as common were headache, motor deficit, hemiparesis, paresis, and dizziness. It confirmed the existence of a correlation between the symptoms arising from the presence of metastasis and its brain location, showing its importance in early diagnosis of metastases. The frontal lobe and the parietal lobe represented the most affected locations by brain metastases. Discussion of results and Concluding Remarks – It verified that tends to be no correlation between the primary location of the tumor and the location of brain metastasis. The number of treated metastases did not suggest an influence on survival after their diagnosis. The realization of surgery and/or administration of whole-brain irradiation therapy prior to radiosurgery showed no prolongation of survival compared with patients that were not submitted to previous treatment.